(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2要讲解和答题
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 11:36:08
(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2要讲解和答题(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2要讲解和答题(x-2
(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2要讲解和答题
(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2
要讲解和答题
(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y),其中x=-1,y=2要讲解和答题
(x-2y)(x+y)-2x(-2x-3y)+6x(-x-y)
=x^2-2xy+xy-2y^2+4x^2+6xy-6x^2-6y^2
=-x^2-8y^2+5xy
x=-1,y=2
原式
=-1-8*4-5*1*2
=-1-32-10
=-43
x(x-y)2-(y-x)3
[2/3x-2/x+y(x+y/3x-x-y)]/x-y/x
化简:{2/3x-2/(x+y)[(x+y)/3x-x-y]}/(x+y)/x
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
化简3x-2/(x+y)[(x+y)/3x-x-y]÷(x-y)/x
因式分解x(x+y)(x-y)-x(x+y)^2
x-y/x-x+y/y-(x+y)(x-y)/y² y/x=2
化简y(x+y)+(x+y)(x-y)-x^2
计算:x+2y/x-y+2x/y-x-3y/x-y
化简:(x-3y)(x+y)-(x-2y)(x+2y)-(x-y)平方
[(3x+y)(x-y)-(2x+3y)(x-y)]*(x-y)
(x+y)(x-y)-(x-y)^2如题 (x+y)(x-y)-(x-y)^2
因式分解3x^2(x-y)+6x(y-x)
【2(x-y)(x-y)(x-y)-8(x-y)(x-y)(x+y)+6y(x-y)(x-y)]/2(x-y)(x-y)
2X(2X-3Y)-3Y(X+Y)
(-2x y)^2-(3y-x)(-x-3y)
(x+2y)^2-(x+y)(3x-y)
计算(x+y)(x+y)^2(-x-y)^3